2009
DOI: 10.5130/lns.v0i0.1276
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up and Moving In: Connecting social practices views to policies and programs in adult education

Abstract: The social practices framework has had a major impact on adult literacy and numeracy research over the past quarter century in the US, the UK and other countries. To date, the social practices view has had far less influence on the development of policies and programs in adult literacy and numeracy education. To help this happen, new kinds of assessment tools aligned with the social practices framework are needed to support appropriate changes in curriculum design, learner assessment and program evaluation.In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 11 publications
5
37
0
Order By: Relevance
“…Our pedagogical focus on social interaction as a key driver of health literacy development is consistent with practice-engagement theory (Reder, 1994, 2009) which “posits that literacy proficiency develops across the lifespan as individuals engage in literacy practices.... Reciprocally, higher levels of literacy proficiency lead to increased engagement in literacy practices” (Reder, in press). As adult ESL learners increase their engagement with new health literacy practices, initially in the classroom, and then eventually in out-of-school contexts (e.g., home, health care settings), they expand their access to institutional, social, and material resources.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Our pedagogical focus on social interaction as a key driver of health literacy development is consistent with practice-engagement theory (Reder, 1994, 2009) which “posits that literacy proficiency develops across the lifespan as individuals engage in literacy practices.... Reciprocally, higher levels of literacy proficiency lead to increased engagement in literacy practices” (Reder, in press). As adult ESL learners increase their engagement with new health literacy practices, initially in the classroom, and then eventually in out-of-school contexts (e.g., home, health care settings), they expand their access to institutional, social, and material resources.…”
Section: Discussionmentioning
confidence: 52%
“…Through meaningful interactions with others (e.g., teachers, more expert peers), ESL learners in turn may adopt new literacy practices for managing preventive health care tasks that they otherwise would not have been able to do alone. Reder’s (2009) longitudinal research on English-proficient adult learners found that the impact of increased practice-engagement on literacy proficiency was significant, but the effects were not immediate: Reder found it took 5–6 years to see the positive impact of practice-engagement on proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…While many researchers favour longitudinal data for investigating age-related change in skills, Salthouse (2009a;2009b;2010b) argued that longitudinal findings on age-skill profiles are too unreliable due to re-test and selection effects. Salthouse maintains that cross-sectional findings provide a more accurate picture of the age-related decline of cognitive skills though these claims are contested by many researchers (e.g., Abrams, 2009;Nilsson et al, 2009;Schaie, 2009).…”
mentioning
confidence: 99%
“…Literacy and numeracy skills are not only a function of formal education but also a wide range of other practices that occur over the lifespan including social and cultural practices, and not least, work practices such as engagement in literacy and numeracy related tasks at work (Desjardins, 2004). Practice engagement is thus important to nurture and develop skills (Reder, 2009a;2009b). By extension workers who are deprived of the opportunity to perform complex literacy tasks may lose some of their skills proficiency.…”
mentioning
confidence: 99%
“…A closely related and often overlapping strand of studies focuses on alternative measures that are more closely tied to the concept of 'skill mismatch', namely 'underskilling' and 'overskilling', or alternatively 'skill deficit' and 'skill surplus/skill underutilization'(see e.g., Krahn & Lowe, 1998;OECD/Statistics Canada, 2005;Mavromaras, McGuinness & Wooden, 2007;Mavromaras, McGuinness & Fok, 2009a;2009b;Mavromaras, McGuinness, O'Leary, Sloane & Wei, 2010;Ryan & Sinning, 2009;OECD/Statistics Canada, 2011). There are fewer studies using the latter concepts partly due to the lack of data and the difficulty in measuring skill mismatch, but the advantages are apparent and interest appears to be on the rise (e.g., CEDEFOP, 2010a).…”
mentioning
confidence: 99%